Student and teacher attitudes towards overtraining and recovery in vocational dance training. Issue 1 (2nd January 2020) - Blevins, Peta; Erskine, Shona; Moyle, Gene; Hopper, Luke
Abstract : Elite performance in dance is the result of many years of training, during which dancers face high physical and emotional demands. There is little empirical evidence addressing dancer training behaviours in the context of overtraining and in response to training demands; however, underlying dancer attitudes that affect training behaviours must first be understood to truly determine the drivers of dance training behaviour. This study explored the attitudes held by vocational dance students and their teachers in relation to stress and recovery during vocational dance training. Using Q methodology with a sample of 86 students and teachers, six viewpoints were identified through factor analyses. These six factors are discussed in relation to the overarching themes of sources of stress, attitudes towards stress and recovery, and dance culture.